From the big bang to planet X : the 50 most-asked questions about the universe--and their answers - Dickinson, Terence (Willowdale, Ont. : Distributed by Firefly Books, 1993)
Fact-filled guide to the latest findings and theories in astronomy.
Adult
Keywords: Astronomy -- Miscellanea; Cosmology -- Miscellanea; Questions and answers; Astronomy -- Miscellanea; Questions and answers; Universe -- Miscellanea